Strategies for Enhancing the New Value Chain of Phrae Nam Prik Larb Business to Drive the Local Economy - Pantang, Paumsak; Buntam, Dussadee; Thamee, Tanakij (Journal of Graduate MCU KhonKaen Campus, 2026)
This study aims to develop strategies for enhancing the new value chain of Phrae-style Nam Prik Larb to increase product value and strengthen the grassroots economy. A mixed methods research design was used, combining Participatory Action Research (PAR) with data collection through semi-structured questionnaires and in-depth interviews involving stakeholders across the entire supply chain. The study also applied the Multi-Criteria Performance Measurement/Analysis Technique (MCPMT) to analyze value addition and income distribution within the product chain. The findings reveal critical weaknesses in the value chain, particularly the limited opportunities for farmers and processors to create added value. Farmers lack Good Agricultural Practices (GAP) systems and face capital shortages, while sellers and collectors receive disproportionately high-profit shares. Consumer awareness of the value of Nam Prik Larb and key spices such as Makwaen (Sichuan pepper) and dried chilli-essential ingredients of the product-remains limited. Although the value addition in the chain is 2.8 times for dried chilli and 5.8 times for Makwaen, these increases are relatively low compared to other agricultural products. This research proposes development strategies based on the Logical Framework Approach and Outcome Mapping, focusing on value restoration for Phrae Nam Prik Larb and Northern Thai spices. It emphasizes product identity creation and entrepreneur capacity building through Regenerative Enterprise principles, coupled with value-driven marketing strategies to empower and sustain the grassroots economy.